TV time - Powell, Jillian; Castro, Andrea (Glasgow : Collins, 2021)
Who will watch TV with Grandpa? Inspire a love of reading with stories that are written from a child's perspective and will encourage children to discover the world around them. With audio and activities, Peapod Readers are the perfect start to a child's journey into learning English. Includes: Before and after reading activities; Picture dictionary; Exam practice; Reading guide online
Primary
Keywords: Families -- Juvenile fiction; Readers (Primary); Readers (Publications); Television -- Juvenile fiction